The impact of land redistribution on the livelihoods of beneficiaries : a case of Molwama Polokwane Province - Makhari, Daisy Jacqueline (My University, 2016)
Land reform in a form of land redistribution has been implemented in developing countries including South Africa. Land reform in South Africa was introduced to address the effects of the racial discrimination practices of the apartheid government, which led to black people being denied access to land prior 1994. The objective of land redistribution is produce commercially viable land reform projects, which will be able to sustain livelihoods of the poor. However evidence from some studies suggest that a large number of these projects have failed. This study aimed to explore the impact of land redistribution programme on the livelihoods of beneficiaries of the Monyamani, Lwalalemetse and Maboi3 (MOLWAMA) farms in the Polokwane municipality, Limpopo province who have benefited from Settlement Land Acquisition Grant (SLAG) a sub-programme of land redistribution. A quantitative research design was used. Data were collected through a semi-structured questionnaire and analysed using the SPSS software. Since the main objective was to determine how the standard of living, the researcher used key indicators such as household income, access to services, production of food for food security, empowerment, security and health. The main findings of the research are that while beneficiaries indicated a positive change on their standard of living, it was evident that because the land was not optimally utilised, the benefits could be much higher but for a number of challenges that they were still experiencing. Beneficiaries highlighted a number of challenges which include water shortages, drought, financial mismanagement, conflict amongst beneficiaries, uncommitted beneficiaries, low wages, low representation of women and youth and lack of financial assistance. In order to resolve these challenges, the study recommends a number of policy interventions. Specifically, on building capacity of beneficiaries by providing entrepreneurship and financial management trainings. The government and other stakeholders should encourage the youth to participate in land reform projects and provide them with necessary skills which, will enable them to work productively. Provision of infrastructure such as access roads, water, electricity and markets is very crucial for successful and sustainable projects.
Thesis (M. Dev.) -- University of Limpopo, 2016
Keywords: Land reform; Land Redistribution of Agricultural Development; Land reform beneficiaries; Land reform -- South Africa